Manajemen Risiko Strategis Bank Syariah - Fikri Al-Haq Fachryana (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2020)
Strategic risk is the risk caused by the implementation and implementation of an improper bank strategy, improper business decision making or the bank not complying / not implementing changes in legislation and other applicable provisions. Strategic Risk Determination Factors and Mitigation: (1) Changes in the map of business competition (The presence of new Islamic banks entering the industry, the emergence of new substitute products) (2) Inaccurate Formulation of Strategy (Strategy not in line with the bank's vision / mission, Analysis of strategic environment not comprehensive, mismatch of strategic plans between strategic levels ) Changes in Stakeholder Behavior. The Risk Management Process in Sharia Banking: (1) Identification of strategic risk, (2) Measurement of strategic risk (3) Monitoring of strategic risk (4) Control of strategic risk (5) Strategic risk management information system.